Facile Preparation of Ni-Co Bimetallic Oxide/Activated Carbon Composites Using the Plasma in Liquid Process for Supercapacitor Electrode Applications - Heon Lee; In-Soo Park; Young-Kwon Park; Kay-Hyeok An; Byung-Joo Kim; Sang-Chul Jung (Nanomaterials, 2019)
In this study, a plasma in a liquid process (PiLP) was used to facilely precipitate bimetallic nanoparticles composed of Ni and Co elements on the surface of activated carbon. The physicochemical and electrochemical properties of the fabricated composites were evaluated to examine the potential of supercapacitors as electrode materials. Nickel and cobalt ions in the aqueous reactant solution were uniformly precipitated on the AC surface as spherical nanoparticles with a size of about 100 nm by PiLP reaction. The composition of nanoparticles was determined by the molar ratio of nickel and cobalt precursors and precipitated in the form of bimetallic oxide. The electrical conductivity and specific capacitance were increased by Ni-Co bimetallic oxide nanoparticles precipitated on the AC surface. In addition, the electrochemical performance was improved by stable cycling stability and resistance reduction and showed the best performance when the molar ratios of Ni and Co precursors were the same.